Technical Efficiency of Oil Palm Production under a Large Agricultural Plot Scheme in Thailand - Cha-on Juyjaeng; Suneeporn Suwanmanee; Panya Mankeb (My University, 2018)
Background and Objective: Thai government launched a Large Agricultural Plot Scheme (LAPS) in 2005 in order to enhance the effectiveness of the extension programme.The objective of this research was to compare the technical efficiency (TE) of oil palm production and factors influencing the TE of oil palm production between member and non-member farmers under the LAPS in Bang Saphan Noi district, Prachuap Khiri Khan Province, Thailand.Methodology: The data were collected from January-June, 2017 from 57 LAPS member farmers and 63 non-LAPS member farmers.This paper estimated technical inefficiency by using a stochastic production frontier model and Tobit regression to investigate the factors influencing the TE.Results: The results revealed that the TE of oil palm production of the LAPS member farmers was ranked 12-99%, whereas that of the non-LAPS member farmers was ranked 14-99%.The TE mean of LAPS member farmers was 0.63, while the TE mean of non-LAPS member farmers was 0.52.The years of experience on oil palm plantations and age were crucial factors that contributed to the TE of LAPS member farmers and TE of non-LAPS member farmers, respectively. Conclusion:The TE mean of LAPS member farmers was higher than that of non-LAPS member farmers knowledge and experience sharing between old and young generations who are eager to work in oil palm production should also be a concern.
Keywords: Plot (graphics); Oil Palm Production and Sustainability